'A fascinating time to be involved with research' exploring the impact of COVID‐19 on postgraduate psycho‐oncology researchers. Issue 4 (9th February 2022) - King, Lucy; Matthews, Sara; Foster, Claire; Starkings, Rachel; Holch, Patricia; Absolom, Kate; Archer, Stephanie; ,
Key points: To explore the COVID‐19 experiences of UK postgraduate research students (PGRs), the British Psychosocial Oncology Society (BPOS) conducted an online survey Twenty‐three respondents' qualitative data were analysed thematically and summarised using the strengths, weaknesses, opportunities, and threats (SWOT) framework COVID‐19 offered opportunities to develop online skills, resilience, and adaptability, whilst opening wellbeing conversations PGRs reported practical difficulties, social isolation, unhealthy work/life balance and concerns about future careers PGRs have had an unprecedented and continually evolving experience; BPOS and relevant institutions must continue to provide adequate support and development opportunities to safeguard their futures